Bioaerosols concentrations in working areas in biomethanization facilities. (2nd November 2017) - Dubuis, Marie-Eve; M'Bareche, Hamza; Veillette, Marc; Bakhiyi, Bouchra; Zayed, Joseph; Lavoie, Jacques; Duchaine, Caroline
ABSTRACT: This study sought to fill the gap in information about the type and the concentration of bioaerosols present in the air of biomethanization facilities (BF). Evaluation of bioaerosol composition and concentration was achieved in two biomethanization facilities located in Eastern Canada, during summer and winter. In order to have a thorough understanding of the studied environment, the methodology combined culture of bacteria and molds, qualitiative polymerase chain reaction (qPCR) for specific microorganisms, endotoxin quantification, and next-generation sequencing (NGS) for bacterial diversity. Results revealed that workers in biomethanization facilities are exposed to bioaerosols and pathogenic microorganisms similar to those found in composting plants. However, human exposure levels to bioaerosols are lower in BF than in composting plants. Despite these differences, use of personal protective equipment is recommended to lower the risks of health problems. Implications : Biomethanization is a new technology used in eastern Canada for waste management. In the next few years, it is expected that there will be an expansion of facilities in response of tight governmental regulations. Workers in biomethanization facilities are exposed to various amounts of bioaerosols composed of some harmful microorganisms. Therefore, monitoring this occupational exposure could be an interesting tool for improving worker's health.